Research on Dehumidifier Performance of Solid Adsorbent for Temperature and Humidity Independent Control - Li Wei; Ge Yanghui; Chen Linan; Zheng Qiao; Chen Wei (Zhileng xuebao)
The adsorption dehumidification performance of Silica gel, zeolite 4A and 13X molecular sieve as a solid desiccant material in a given fixed bed is experimentally studied for different combinations and filling. The fixed bed temperature and productivity change with time is analyzed during the adsorption dehumidification phase. The energy saving effect of the different combination of solid adsorbent and means of filling is analyzed with the adsorption efficiency evaluation index in adsorption process. The results show thatthe solid desiccant combination and filling method with silicone + 13X molecular sieve is more suitable for the fixed bed of solid adsorbent in the parameters condition of experiment.